Benefits of Moringa Leaves ( Moringa Oleifera ) as A Source of Functional Food And Herbal Medicine - Maraniati, Maraniati (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2024)
Moringa Oleifera is classified as a nutraceutical plant due to its nutritional value and medicinal properties. However, it lags behind in popularity compared to Zingiberaceae. Therefore, there is a need for a comprehensive study to explore the benefits and potential use of Moringa Oleifera. This research aims to extensively discuss the applications of Moringa Oleifera as a food and medicine ingredient, based on thorough literature review. The literature was obtained online using Google scholar with relevant keywords such as Moringa Oleifera, uses of Moringa Oleifera, and bioactivities of Moringa Oleifera. The study reveals that Moringa Oleifera demonstrates a broad range of therapeutic effects, including antimicrobial, anticancer, hepatoprotective, anti-diabetes mellitus, and antioxidant activities. It contains significant nutrients and compounds, particularly in the leaves, making it a potential solution for addressing malnutrition. Therefore, Moringa Oleifera presents itself as a promising food alternative that can effectively combat malnutrition while also providing pharmaceutical benefits.